Diagnosis and management of differentiated thyroid cancer using molecular biology1. (12th February 2013) - Witt, Robert L.; Ferris, Robert L.; Pribitkin, Edmund A.; Sherman, Steven I.; Steward, David L.; Nikiforov, Yuri E.
Abstract Objectives/Hypothesis: To define molecular biology in clinical practice for diagnosis, surgical management, and prognostication of differentiated thyroid cancer. Data Sources: Ovid Medline 2006‐2012 Review Methods: Manuscripts with clinical correlates. Results: Papillary thyroid carcinomas harbor point mutations of the BRAF and RAS genes or RET/PTC rearrangements, all of which activate the mitogen‐activated protein kinase pathway. These mutually exclusive mutations are found in 70% of PTC. BRAF mutation is found in 45% of papillary thyroid cancer and is highly specific. Follicular carcinomas are known to harbor RAS mutation or PAX8/PPARγ rearrangement. These mutations are also mutually exclusive and identified in 70% of follicular carcinomas. Molecular classifiers measure the expression of a large number of genes on a microarray chip providing a substantial negative predictive value pending further validation. Conclusions: 1) 20% to 30% of cytologically classified Follicular Neoplasms and Follicular Lesion of Undetermined Significance collectively are malignant on final pathology. Approximately 70% to 80% of thyroid lobectomies performed solely for diagnostic purposes are benign. Molecular alteration testing may reduce the number of unnecessary thyroid procedures, 2) may reduce the number of completion thyroidectomies, and 3) may lead to more individualized operative and postoperative management. Molecular testing for BRAF, RAS, RET/PTC, and PAX8/PPARγ for follicular lesion of undetermined significance and follicular neoplasm improve specificity, whereas molecular classifiers may add negative predictive value to fine needle aspiration diagnosis.